DEVELOPMENT OF E - ACCOUNTING MODULE TO IMPROVE STUDENT'S LEARNING ACHIEVEMENT - Dirmansah Dirmansah; Bambang Sahono (UNIB Press, 2019)
This research aims to improvetheLearning Achievement ofeconomic subjects of the XIIIP SstudentsinSMANegeri1Gumay TalangLahat throughthe developmentof Accounting E-Module withthe subjectof the researchare two economic techersand Studentsof XIIIPS are 30 students, Studentsof XIIIPS2 are 30 students as the experimental class, students of XIIIPS3 are 30 students asthe controlclass.The objectof the research is theE-Module Accounting. The result sof the data analysis sho wthat:a)ThedevelopedE-ModuleofAccounting isappropriate toimprove student achievementin economic subjectsinthe XII grade social studiesat SMA Negeri1Gumay TalangLahat,b)TheE-Moduleof Accountingdeveloped is ateaching material very effectivewayto improve student achievement in class XIIIPSat GumayTalang Lahat SeniorHigh School